Exploring Players’ Perceptions of the Haptic Feedback in Haptic Digital Games - Kirginas,Sotiris, (2022)
Abstract This study explores the added value of haptic digital games as a novel and innovative form of human-computer interaction that complements and enriches traditional forms of visual and auditory communication. In light of the limited number of empirical studies in this area, the statement above becomes more significant. The use of haptic digital games becomes especially important when we consider that these games are not just passive digital applications where users do not act and passively receive information on their skin. Haptic interaction is an active form of communication in which the user receives information through vibrations, rumbles, pulses or thermal feedback on their body. Users intentionally choose their actions when exploring and manipulating an object or situation. These actions provide information about the properties of objects and thus give the player helpful feedback that affects the game experience. The main objectives of this qualitative study was to examine and clarify the features of haptic digital games that (a) increase player immersion and player engagement in the game, (b) make the game experience more realistic and compelling, and (c) distract or disengage them.